FEATURES OF PLASMAPHERESIS IN THE TREATMENT OF GRAFT REJECTION AFTER KIDNEY TRANSPLANTATION - A. V. Vatazin; A. B. Zulkarnaev; R. O. Kantarija; M. Krstich; A. P. Faenko (Вестник трансплантологии и искусственных органов, 2015)
Introduction. The development of immunological confl ict in the form of host-versus-graft reaction has always been main problem in transplantation. The worst case is the development of humoral rejection with the presence of circulating immune complexes and antibodies. There are several methods for quick removal of antibodies; among those are traditional plasmapheresis (PA) and double fi ltration plasmapheresis (DFPF). In this paper we present our experience with these two methods and give a comparative evaluation of the effectiveness in the treatment of acute humoral rejection in renal allograft. Aim: to compare the effectiveness of traditional and double fi ltration plasmapheresis while processing different volumes of plasma in the treatment of host-versus-graft disease after kidney transplantation.Methods. The study included 58 patients after kidney transplantation. All patients had increased activity of humoral immunity, which was confi rmed by immunofl uorescence with luminescence C4d complement component. In 26 patients we performed DFPF, in 32 patients – traditional PA. We divided the DFPF patients into 4 subgroups depending on the amount of processed plasma: > 50% (5 patients), 50–100% (8 patients), 100–150% (7 patients), 150–200% (6 patients) of circulating plasma volume. We also divided PA patients into four subgroups depending on the volume of plasma removed: >50% (8 patients), 50–70% (12 patients), 70–90% (7 patients), 90–110% (5 patients) of the volume of circulating plasma. We monitored the immune status with markers of humoral immunity activation IgM, IgG before and after each of the procedures.Results. Each procedure of traditional PA and DFPF was accompanied by a marked decrease in blood concentrations of IgM and IgG antibodies. Their level decreased by an average of 30–55% of the original. However, some patients in both groups showed an increase in the concentration of these immunoglobulins in 1–2 days after the fi rst and the second procedures. The effect of rebound was observed during DFPF if in one procedure less than 100% of the circulation plasma volume was processed and during traditional PA if less than 70% was removed. Upon reaching the target values and increasing the processing volumes we managed to avoid growth of IgM and IgG.Conclusions. DFPF and traditional PA can effectively reduce the high titers of circulating antibodies, which is accompanied by a decrease in the activity of humoral immunity of the recipient. In the case of double fi ltration plasmapheresis at least one volume of circulating plasma should be processed and in traditional plasmapheresis – at least 70% should be removed.